2015
DOI: 10.1073/pnas.1518028112
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule visualization of RecQ helicase reveals DNA melting, nucleation, and assembly are required for processive DNA unwinding

Abstract: DNA helicases are motor proteins that unwind double-stranded DNA (dsDNA) to reveal single-stranded DNA (ssDNA) needed for many biological processes. The RecQ helicase is involved in repairing damage caused by DNA breaks and stalled replication forks via homologous recombination. Here, the helicase activity of RecQ was visualized on single molecules of DNA using a fluorescent sensor that directly detects ssDNA. By monitoring the formation and progression of individual unwinding forks, we observed that both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 69 publications
5
37
0
Order By: Relevance
“…In many cases, there is evidence that helicases can behave as tandem assemblies while acting upon nucleic acids, and that the changes in their oligomeric state regulate their activities (Lohman et al, 2008). Specific examples of tandem helicase assemblies include the bacteriophage T4 SF1 helicase DdaA (Byrd and Raney, 2004), the hepatitis C virus Sf2 helicase NS3 (Levin et al, 2004), and E. coli RecQ (Rad et al, 2015). In addition, recent studies have shown that E. coli UvrD translocates either as a monomer or as two tandem monomers, and that the tandem monomers are more processive than a single monomer (Comstock et al, 2015; Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, there is evidence that helicases can behave as tandem assemblies while acting upon nucleic acids, and that the changes in their oligomeric state regulate their activities (Lohman et al, 2008). Specific examples of tandem helicase assemblies include the bacteriophage T4 SF1 helicase DdaA (Byrd and Raney, 2004), the hepatitis C virus Sf2 helicase NS3 (Levin et al, 2004), and E. coli RecQ (Rad et al, 2015). In addition, recent studies have shown that E. coli UvrD translocates either as a monomer or as two tandem monomers, and that the tandem monomers are more processive than a single monomer (Comstock et al, 2015; Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Helicases are enzymes that play an important role in almost every aspect of RNA and DNA metabolism [1][2][3][4][5][6][7]. This class of molecular motors, which has been grouped into six super families, utilize the free energy from ATP hydrolysis to translocate directionally over hundreds of bases on single-strand (ss) nucleic acids.…”
Section: Introductionmentioning
confidence: 99%
“…A complete understanding requires direct measurement of individual events that make up the distribution of behaviors that comprise the ensemble. In recent decades, we have used single-molecule imaging to visualize the movement and actions of DNA motor proteins (Amitani, Baskin, & Kowalczykowski, 2006; Bianco et al, 2001; Handa, Bianco, Baskin, & Kowalczykowski, 2005; Liu, Baskin, & Kowalczykowski, 2013; Nimonkar, Amitani, Baskin, & Kowalczykowski, 2007; Rad, Forget, Baskin, & Kowalczykowski, 2015; Spies, Amitani, Baskin, & Kowalczykowski, 2007; Spies et al, 2003; Amitani, Liu, Dombrowski, Baskin, & Kowalczykowski, 2010; Forget, Dombrowski, Amitani, & Kowalczykowski, 2013; Hilario & Kowalczykowski, 2010; Sun & Wang, 2016). Here, we limit ourselves to a description of some of those methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study of protein–DNA interactions at the single-molecule level is supported by a wide range of complementary techniques, including, but not limited to, atomic force microscopy, electron microscopy, force spectroscopy, fluorescence correlation spectroscopy, Förster resonance energy transfer, magnetic tweezers, optical traps combined with fluorescence microscopy, and total internal reflection fluorescence (TIRF) microscopy (Bustamante, Bryant, & Smith, 2003; Greenleaf, Woodside, & Block, 2007; Ha, Kozlov, & Lohman, 2012; Kapanidis & Strick, 2009; Lionnet et al, 2012; Moffitt, Chemla, Smith, & Bustamante, 2008; Neuman & Nagy, 2008; Qi & Greene, 2016; Roy, Hohng, & Ha, 2008; Spies, 2013; Yodh, Schlierf, & Ha, 2010). Mechanical manipulation of individual DNA molecules by optical trapping of attached microspheres or by attachment to a surface has been a useful platform for studying the mechanisms of DNA helicases and translocases (Amitani et al, 2006, 2010; Bianco et al, 2001; Forget et al, 2013; Hilario & Kowalczykowski, 2010; Liu et al, 2013; Rad et al, 2015; Sun & Wang, 2016). …”
Section: Introductionmentioning
confidence: 99%